2019
DOI: 10.1007/s00348-019-2854-7
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale volumetric flow visualization of the unsteady wake of a flapping-wing micro air vehicle

Abstract: The objective of this experimental investigation is the volumetric visualization of the near wake topology of the vortex structures generated by a flapping-wing micro air vehicle. To achieve the required visualization domain (which in the present experiments amounts to a size of 60,000 cm 3 ), use is made of robotic particle image velocimetry, which implements coaxial illumination and imaging in combination with the use of helium-filled soap bubbles as tracer particles. Particle trajectories are determined via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…These issues could in principle be resolved with a volumetric visualization approach at a sufficiently large scale, but this is currently not yet achievable with off-the-shelf PIV equipment. Although a few large-scale volumetric studies have been reported [23,24], the general applicability of such approaches is currently limited by the required high laser power for the volume illumination, the low-to-moderate repetition rate of these PIV lasers, and, in consequence of the latter, the necessity for phase-averaging data strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues could in principle be resolved with a volumetric visualization approach at a sufficiently large scale, but this is currently not yet achievable with off-the-shelf PIV equipment. Although a few large-scale volumetric studies have been reported [23,24], the general applicability of such approaches is currently limited by the required high laser power for the volume illumination, the low-to-moderate repetition rate of these PIV lasers, and, in consequence of the latter, the necessity for phase-averaging data strategies.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the flow structures that are observed in the measurement plane depend on both the position of the MAV relative to the light sheet, as well as on the flapping phase of the wings, and can be further complicated when the MAV crosses the plane with a yaw or sideslip angle. Removal of this ambiguity in the flow visualization would best be served by a true volumetric method, see e.g., [23,24], but such is as yet not really feasible for the considered conditions. Nevertheless, the obtained results were found to be informative regarding the generation of streamwise vortical structures during the flapping cycle.…”
Section: Spanwise Planar Flow Visualizationsmentioning
confidence: 99%
“…Optical measurements of the unsteady flow field and the structural motion are performed in an integrated manner, using the same PTV data acquisition and processing system. Particle tracking velocimetry via the Lagrangian particle tracking algorithm Shake-The-Box [10] using helium-filled soap bubbles as flow tracers [11] is a technique that is suitable for the measurement of large-scale unsteady flow fields [12][13][14] and can also be used to perform photogrammetric tracking of fiducial markers on moving objects in the flow [15]. After the PTV measurements of the flow and the structural motion are obtained, physical models need to be applied to determine the unsteady interaction of the forces of different nature on the wing.…”
Section: Aeroelasticity Dynamicmentioning
confidence: 99%
“…To simulate this in the windtunnel, the parameters θb, f, and Unormal∞ were set to replicate values measured in previous free forward flight investigations. 9,12 The cases investigated here are shown in Table 1. The Reynolds number, based on freestream velocity and mean wing chord, varies between Re 2600 and 12,000 for these cases.…”
Section: Wing Deformation In Forward Flightmentioning
confidence: 99%
“…This MAV features two wing pairs in an X-wing configuration, which “clap-and-peel” 5 on each side. Several studies of the force production 9 and flow field around the DelFly have already been carried out 1012 ; however, the wing deformation was treated comparatively little. 7 So far, the deformation was considered to be purely symmetrical, as only a stationary hover case was studied.…”
Section: Introductionmentioning
confidence: 99%